Digitalisasi Layanan Administrasi Akademik dalam Meningkatkan Mutu Pelayanan Pendidikan di MAS Proyek UNIVA Medan - Alyani, Filza; Marpaung, Syafri Fadillah (Jurnal Pendidikan Madrasah, 2026)
The transformation of educational administration through digitalization has become a strategic necessity in improving the effectiveness, transparency, and quality of academic services in educational institutions. However, many madrasahs still encounter challenges related to technological infrastructure, digital literacy, and organizational readiness in implementing digital-based administrative systems. This study aims to analyze the implementation of educational digitalization, the organization of supporting resources, and the evaluation mechanisms in improving the quality of academic administrative services at MAS Proyek UNIVA Medan. This research employed a qualitative case study approach involving the principal, vice principal, teachers, administrative staff, operators, and students selected purposively. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that digitalization has been implemented through various integrated platforms such as CBT, RDM, EMIS, Simpatika, Google Classroom, Zoom Meeting, and ALEF Education. The implementation has improved service efficiency, data accuracy, accessibility, transparency, and administrative effectiveness. Resource organization has been conducted systematically through the strengthening of human resources, technological infrastructure, and integrated information systems. Evaluation mechanisms are carried out continuously through monitoring, technical improvement, and adaptive service strategies. This study contributes to strengthening the discourse on digital transformation management in Islamic educational institutions, particularly regarding the integration of digital administration systems and academic service quality improvement.